Effects of protocol on prevention of delirium in hospitalized hip fracture patients: A quality improvement project. (February 2020) - Durst, Jennifer; Wilson, Denise
Abstract: Background: Delirium is a sudden change of consciousness experienced by hospitalized patients that results in negative outcomes. The incidence of delirium is under-reported and can be prevented in many patients. The purpose of this evidence-based study was to determine if the incidence of delirium decreased with the use of prevention interventions for hip fracture patients. Methods: The project was a prospective quality improvement project. An audit of medical records using the CHART-DEL instrument was conducted pre- and post-implementation of an evidence-based protocol. Medical records were reviewed until discharge for the use of prevention interventions and the diagnosis of delirium. Results: The sample included 90 hip fracture patients, 45 patients in both the pre- and post-implementation groups. The hip fracture protocol was used by admitting physicians in 31% of admissions and prevention interventions were documented by nurses in 75.6% of medical records. The incidence of delirium was similar in both groups; 11.1% in the pre-implementation group and 15.6% in the post-implementation group and was not statistically significant. Discussion: Healthcare workers should take measures to reduce the incidence of delirium. There is a need for further studies on the use of protocols in the identification, prevention, and treatment of delirium in hospitalized patients.